Penerapan Sistem Informasi Akuntansi Menggunakan Software Accurate dalam Pengambilan Keputusan UMKM di Kota Mataram - Cahyani, Suci; Nurabiah, Nurabiah (Puslitbang Sinergis Asa Professional, 2024)
Accurate is an accounting information system that is useful for facilitating the management of financial data for companies and MSMEs and producing information in the form of financial reports that can be used as a basis for decision making. So far there are still many MSMEs that have not implemented accounting information systems such as accurate software. This research is intended to find out how to implement an accounting information system using accurate software in decision making for MSMEs in Mataram City. The research method used was descriptive qualitative with data collection techniques through interviews and documentation with informants, namely each owner or manager and employees responsible for implementing Accurate Software from 4 MSMEs in Mataram City, including CV. Prabu Pande Perkasa, CV. Lancar Jaya Abadi, Geshuter Lombok, and Mahkota Lancar. The results of this research can be concluded that the application of Accurate Software to several MSMEs in Mataram City can be said to be quite effective according to TAM theory even though there is one drawback related to invoices which shows that there is an additional need for data processing. Then, in making decisions, MSMEs tend to take low risks, pay attention to basic information, and must have creative thinking.